The impact of minimally-invasive esophagectomy operative duration on post-operative outcomes - Tupper, Haley I.; Roybal, Belia O.; Jackson, Riley W.; Banks, Kian C.; Kwak, Hyunjee V.; Alcasid, Nathan J.; Wei, Julia; Hsu, Diana S.; Velotta, Jeffrey B. (Frontiers in Surgery, 2024)
Background: Esophagectomy, an esophageal cancer treatment mainstay, is a highly morbid procedure. Prolonged operative time, only partially predetermined by case complexity, may be uniquely harmful to minimally-invasive esophagectomy (MIE) patients for numerous reasons, including anastomotic leak, tenuous conduit perfusion and protracted single-lung ventilation, but the impact is unknown. This multi-center retrospective cohort study sought to characterize the relationship between MIE operative time and post-operative outcomes. Methods: We abstracted multi-center data on esophageal cancer patients who underwent MIE from 2010-2021. Predictor variables included age, sex, comorbidities, body mass index, prior cardiothoracic surgery, stage, and neoadjuvant therapy. Outcomes included complications, readmissions, and mortality. Association analysis evaluated the relationship between predictor variables and operative time. Multivariate logistic regression characterized the influence of potential predictor variables and operative time on post-operative outcomes. Subgroup analysis evaluated the association between MIE >4 hours versus <4 hours and complications, readmissions and survival. Results: For the 297 esophageal cancer patients who underwent MIE between 2010-2021, the median operative duration was 4.8 hours [IQR: 3.7-6.3]. For patients with anastomotic leak (5.1%) and 1-year mortality, operative duration was elevated above the median at 6.3 hours [IQR: 4.8-8.6], p=0.008) and 5.3 hours [IQR: 4.4-6.8], p=0.04), respectively. In multivariate logistic regression, each additional hour of operative time increased the odds of anastomotic leak and 1-year mortality by 39% and 19%, respectively. Conclusions: Esophageal cancer is a poor prognosis disease, even with optimal treatment. Operative efficiency, a modifiable surgical variable, may be an important target to improve MIE patient outcomes.